Reconstruction Of Asset Confiscation Through the Non-Conviction-Based Asset Forfeiture Reviewed In Maslahah Mursalah - Khairatul Anisa; Abdul Fattaah (JURNAL ILMU SYARIAH, 2026)
Abstract Efforts to eradicate corruption in Indonesia have so far been less than optimal because they have focused solely on prosecuting perpetrators and have paid insufficient attention to recovering losses to the state. The Non-Conviction-Based Asset Forfeiture (NCB) mechanism, as outlined in the draft asset forfeiture law, is a regulatory framework designed to facilitate the recovery of state funds and the eradication of corruption. The objectives of this study are, first, to explain the draft asset forfeiture law and its Non-Conviction-Based Asset Forfeiture mechanism. Second, to examine the public interest from the perspective of Islamic law regarding asset recovery through the Non-Conviction-Based Asset Forfeiture (NCB) mechanism and to analyze the implementation of NCB in countries that have adopted it, so that regulations in Indonesia do not focus solely on punishing perpetrators but also on recovering state financial losses, assess their public interest, and ensure they do not conflict with the values of Islamic law. The results of this study indicate that the application of NCB in the Asset Forfeiture Bill does not conflict with the concept of al-bara’ah al-ashliyyah (the presumption of innocence), does not pose a risk of violating human rights, and does not violate the principle of hifz mal. Keywords: Corruption; Non-Conviction Based Asset Forfeiture (NCB); benefit